Quality Management System and Audit Quality: The Moderating Effect of Independent Audit Inspection in China - Yuqing Zheng; Noor Adwa Sulaiman; Suhaily Shahimi (Asian Journal of Accounting Perspectives, 2023)
Research aim: This study examines the effect of quality management systems (QMS), in terms of leadership responsibility, relevant ethical requirements, human resource, engagement performance, and monitoring, on audit quality (AQ). Also, this study examines whether independent audit inspection moderates the relationship between QMS and AQ. Design/ Methodology/ Approach: A total of 414 external auditors working in Chinese accounting firms responded to the online survey questionnaires. Research finding: By using SmartPLS as a tool for data analysis, the results showed that all elements of the quality QMS have positive effect on AQ. However, it failed to establish the moderating effect of an independent audit inspection on QMS and AQ. Theoretical contribution/ Originality: This study contributes to elucidating the significance of QMS in promoting AQ, as well as shedding light on the ongoing debate regarding the impact of independent audit inspection on AQ. Practitioner/ Policy Implication: Public accounting firms and regulators should focus on improving QMS to ensure high audit quality.